An evaluation of the competencies of primary health care clinic nursing managers in two South African provinces. Issue 1 (1st December 2016) - Munyewende, Pascalia O.; Levin, Jonathan; Rispel, Laetitia C.
Abstract : Background: Managerial competencies to enhance individual and organisational performance have gained currency in global efforts to strengthen health systems. Competent managers are essential in the implementation of primary health care (PHC) reforms that aim to achieve universal health coverage. Objective: To evaluate the competencies of PHC clinic nursing managers in two South African provinces. Design: A cross-sectional study was conducted in two South African provinces. Using stratified random sampling, 111 PHC clinic nursing managers were selected. All supervisors ( n =104) and subordinate nurses ( n =383) were invited to participate in the survey on the day of data collection. Following informed consent, the nursing managers, their supervisors, and subordinate nurses completed a 40-item, 360-degree competency assessment questionnaire, with six domains: communication, leadership and management, staff management, financial management, planning and priority setting, and problem-solving. Standard deviations, medians, and inter-quartile ranges (IQRs) were computed separately for PHC nursing managers, supervisors, and subordinate nurses for competencies in the six domains. The Tinsley and Weiss index was used to assess agreement between each of the three possible pairs of raters. Results: A 95.4% response rate was obtained, with 105 nursing managers in Gauteng and Free State completing the questionnaires. There was a lack of agreement about nursing managers' competencies among the three groups of raters. Overall, clinic nursing managers rated themselves high on the five domains of communication (8.6), leadership and management (8.67), staff management (8.75), planning and priority setting (8.6), and problem-solving (8.83). The exception was financial management with a median score of 7.94 (IQR 6.33–9.11). Compared to the PHC clinic managers, the supervisors and subordinate nurses gave PHC nursing managers lower ratings on all six competency domains, with the lowest rating for financial management (supervisor median rating 6.56; subordinate median rating 7.31). Conclusion: The financial management competencies of PHC clinic nursing managers need to be prioritised in continuing professional development programmes.